Respostas morfofisiológicas e bioquímicas em mudas de Eucalyptus urograndis e Hymenaea courbaril L. após a rustificação - Rocha , Maria Eunice Lima (2022)
In the seedling production phase, hardening can be implemented in order to improve seedling quality and to increase tolerance to external conditions after planting. The hardening of eucalyptus and jatoba seedlings can change the morphophysiological characteristics, as a defense strategy against the controlled stress caused by these practices, as well as attenuating the stress conditions, especially the water stress. Thus, based on the above, the objective of the research was to quantify the morphological, physiological and biochemical changes from chemical and mechanical hardening in Eucalyptus urograndis and Hymenaea courbaril seedlings as a function of growth stages. The experiments were carried out in a protected environment, belonging to Unioeste, Campus Marechal Cândido Rondon (PR). In the first experiment, the purpose was to quantify the growth of the hybrid and the species, as well as the determination of the stages in order to employ the hardening treatments. The design used was completely randomized, composed of 16 and 12 evaluations for eucalyptus and jatobá, respectively. The determinations consisted of morphometric quantifications and growth rates. The stages were chosen based on the accelerated, intermediate and slow growth, including, 70, 100 and 130 days in the case of eucalyptus and 50, 80 and 110 days in jatoba seedlings. Furthermore, in the second and third experiments, the experimental design used was completely randomized, consisting of three treatments (control, methyl jasmonate and stem bending) with seven replications of 30 seedlings each in eucalyptus, while in jatoba seven replications were used of 16 seedlings each. The analyzes consisted of the morphometric and physiological parameters, as well as the survival of seedlings in the field. In the field phase, in jatoba seedlings there was no difference between treatments and growth stages when evaluating survival. Finally, in the last chapter, the hardened seedlings were submitted to water deficit in order to quantify the osmotic adjusters present in the cells and tissues, such as the leaf temperature in the two species as a function of the growth stages. The solute content was altered as a function of the stressful condition in eucalyptus and jatoba seedlings and as the water content decreased, the amino acid, proline and glycine content increased.